Building community-based HIV and STI prevention programs on the tundra: drawing on Inuit women’s strengths and resiliencies - Rand, Jenny Rebekah (2014)
There is a dearth of literature to guide the development of community-based HIV and Sexually Transmitted Infection (STI) prevention and sexual health promotion programs within Inuit communities. The aim of this research project was to create a dialogue with Inuit women to inform future development of such programs. This study employed Indigenous methodologies and methods by drawing from Inuit Qaujimajatuqangit and postcolonial research theory in a framework of Two-Eyed Seeing, and utilizing storytelling sessions to gather data. Community-Based Participatory Research Principles informed the design of the study, ensuring participants were involved in all stages of the project. Nine story-sharing sessions took place with 21 Inuit women ages 18-60. Participants identified several key determinants of sexual health and shared ideas for innovative approaches that they believe will work as prevention efforts within their community. These research results build upon the limited knowledge currently available about perceptions of HIV and STI among Inuit women living in the remote north. Graduate 0573 jenny.r.rand@gmail.com